Description of two new species of Pheles Herrich-Schäffer, [1853] and notes on the taxonomic position of two species hitherto included in the genus (Riodinidae: Riodininae) - Dias, Fernando Maia Silva; Dolibaina, Diego Rodrigo; Mielke, Carlos Guilherme Costa; Mielke, Olaf Hermann Hendrik; Casagrand, Mirna Martins (Zootaxa, 2015)
Two new species of Pheles Herrich–Schäffer, [1853], Pheles plaumanni Dolibaina & Dias sp. nov. and Pheles obscura C. Mielke, Dolibaina & Dias sp. nov. are described from southern Brazil. Through the comparative study of the morphology of the head, labial palpus and the genitalia two species are removed from Pheles and the following new combinations are proposed: Pachythone bicolor (Godman & Salvin, 1886) comb. nov. and Melanis caatingensis (Callaghan & Nobre, 2014) comb. nov. The species studied are pictured and details of the head and genitalia are illustrated.